Effects of Sexual Preferences on Earnings in the Netherlands - Erik Plug; Peter Berkhout (Institute for the Study of Labor (IZA), 2001)
A small literature suggests that bisexual and homosexual workers earn less than their heterosexual fellow workers and that a discriminating labor market is partly to blame. In this paper we examine whether sexual preferences affect earnings in the beginning of working careers in the Netherlands. We find (i) that young and highly educated gay male workers earn about 3 percent less than heterosexual men; (ii) that similarly qualified lesbian workers earn about 4 percent more than their heterosexual female coworkers; (iii) that in terms of earnings, bisexual workers are more comparable to heterosexual workers; and (iv) that among homosexual workers the gender gap is not observed. From this we conclude that the Dutch labor market does not discriminate on the basis of both sexual orientation and gender in entry level jobs.
Keywords: J71; J15; J16; 330; Earnings; sexual preferences; gender differences; discrimination; Lohndifferenzierung; Sexualität; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Schätzung; Niederlande